2022
DOI: 10.1038/s41420-022-01096-0
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR/miR-1277-5p/ZEB1 axis mediates hypoxia-induced oxaliplatin resistance via regulating epithelial-mesenchymal transition in colorectal cancer

Abstract: The hypoxic microenvironment contributes to the chemoresistance of many malignant tumors including colorectal cancer (CRC). Accumulating studies have indicated that long non-coding RNAs (lncRNAs) play important roles in chemotherapy resistance. In this study, we aimed to determine the effect of lncRNAs in hypoxia-mediated resistance in CRC and its potential mechanism. Here, we discovered that hypoxia-induced oxaliplatin resistance and HOX transcript antisense RNA (HOTAIR) expression was increased in hypoxia-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…CAFs transfer exosomes miR-92a-3p and lncRNA H19 into CRC cells, activate Wnt/β-catenin, mediate EMT, and promote CRC stemness and 5-FU/OXA resistance ( 135 , 155 ). The hypoxic HOTAIR/miR-1277-5p/ZEB1 axis mediated oxaliplatin resistance in CRC ( 156 , 157 ). Hypoxia can also interact with other mechanisms, such as activating cytochrome P450 subtype CYP3A6 and accelerating drug metabolism; it can also induce ABC transporter upregulation and promote drug efflux ( 158 ).…”
Section: Tcm Reverses the Chemoresistance Of Crc And Inhibits Tumor G...mentioning
confidence: 99%
See 1 more Smart Citation
“…CAFs transfer exosomes miR-92a-3p and lncRNA H19 into CRC cells, activate Wnt/β-catenin, mediate EMT, and promote CRC stemness and 5-FU/OXA resistance ( 135 , 155 ). The hypoxic HOTAIR/miR-1277-5p/ZEB1 axis mediated oxaliplatin resistance in CRC ( 156 , 157 ). Hypoxia can also interact with other mechanisms, such as activating cytochrome P450 subtype CYP3A6 and accelerating drug metabolism; it can also induce ABC transporter upregulation and promote drug efflux ( 158 ).…”
Section: Tcm Reverses the Chemoresistance Of Crc And Inhibits Tumor G...mentioning
confidence: 99%
“…TAM secretes IL-6 and MFG-E8, respectively, activates the IL-6R/ STAT3 and Hedgehog pathways, induces CSCs, and shields CSCs from the cytotoxic effects of 5-FU and cisplatin, resulting in treatment resistance and recurrence (152-154). CAFs transfer exosomes miR-92a-3p and lncRNA H19 into CRC cells, activate Wnt/b-catenin, mediate EMT, and promote CRC stemness and 5-FU/OXA resistance (135,155). The hypoxic HOTAIR/miR-1277-5p/ZEB1 axis mediated oxaliplatin resistance in CRC (156,157).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Notably, emerging evidence has revealed that lncRNAs could target mRNAs to promote chemoresistance[ 84 ]. For instance, upregulation of the lncRNA HOTAIR has been reported to facilitate EMT in a ZEB1-dependent manner by negatively regulating miR-1277-5p, a process that is involved in hypoxia-induced oxaliplatin resistance[ 85 ]. We previously discovered that metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was overexpressed in CRC tissues compared to paired noncancerous tissues.…”
Section: Overview Of the Regulatory Roles Of Ncrnas In Crc Oxaliplati...mentioning
confidence: 99%
“…LncRNAs change the therapeutic effects of multiple drugs on cancer. LncRNA-Hotair regulates the EMT-related signaling pathway by altering hypoxia-induced oxaliplatin resistance ( 37 ). Overexpression of lncRNA-NORAD affects the EMT process by interacting with hsa-miR-125a-3p, thus promoting the invasion and migration in vitro and in vivo ( 38 ).…”
Section: Lncrnas In Carcinogenesismentioning
confidence: 99%